United Arab Emirates : Technical Assistance Report-Hedonic Methods for Price Indices Mission. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2022)
A technical assistance (TA) mission was conducted remotely during January 16-20, 2022 to assist the Dubai Statistics Center (DSC) in introducing hedonic methods for quality adjustments in the consumer price index (CPI) and the real estate price index (REPI). Currently the REPI is compiled by DSC using stratification with simple averages. Moving from simple averages to hedonic regressions will improve the accuracy of the indicator since it will take into account the quality mix of properties within each stratum. The mission recommended the hedonics time dummy method with a rolling window of 12 months for compiling the REPI. This method provides more stable results, id est, less volatile indices, since it pools one year of data instead of one quarter, and it is particularly recommended when few observations are available. It is widely used for Residential Property Price Index compilation and for CPI compilation with web scraped data. The TA mission provided extensive training on using this method accompanied by R codes adapted to the Dubai sample data.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; United Arab Emirates